2003
DOI: 10.2209/tdcpublication.44.133
|View full text |Cite
|
Sign up to set email alerts
|

A Cineradiographic Study of Deglutitive Tongue Movement in Patients With Anterior Open Bite

Abstract: The purpose of this study was to use cineradiographic images to investigate tongue movement during deglutition in anterior open bite patients with tongue thrust. Each subject had semi-spherical lead markers attached to the tip and dorsal surface of the tongue and was asked to swallow 5 ml of diluted liquid barium. Tongue movement during deglutition was recorded in the mid-sagittal plane with an X-ray VTR system. The deglutition process was divided into 6 stages to analyze the movements of the tip and dorsal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 5 publications
(3 reference statements)
0
19
0
5
Order By: Relevance
“…Proffit et al [27] assume an unknown post-operative change mechanism in the tongue-rest position. Kawamura et al [21] explained this by the anterior position of the tip and back of the tongue in open bite so that the tongue's tip is pressed against the incisors. In this study, we observed soft-tissue dysfunction as a decisive factor in vertical relapse.…”
Section: Diskussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proffit et al [27] assume an unknown post-operative change mechanism in the tongue-rest position. Kawamura et al [21] explained this by the anterior position of the tip and back of the tongue in open bite so that the tongue's tip is pressed against the incisors. In this study, we observed soft-tissue dysfunction as a decisive factor in vertical relapse.…”
Section: Diskussionmentioning
confidence: 99%
“…Proffit et al [27] gehen von einem unbekannten Mechanismus der postoperativen Änderung der Zungenruhelage aus. Dieser wird von Kawamura et al [21] in dem Sinne erklärt, dass bei offenem Biss sowohl die Zungenspitze als auch der Zungenrücken anterior positioniert werden, so dass die Zungenspitze gegen die Inzisiven gedrückt wird. In der vorliegenden Untersuchung konnten die Weichteildysfunktionen als entscheidende Faktoren für ein Rezidiv in der Vertikalen herausgearbeitet werden.…”
Section: Diskussionunclassified
“…From a clinical point of view, tongue performance during swallowing also depends on the maxillomandibular relationship and occlusion, especially in the case of an anterior open bite [40,41]. Periodontal mechanoreceptors of a hypofunctional tooth demonstrated atrophic change in histologic and physiologic aspects [42,43].…”
Section: Physiologic Mechanism Of Swallowingmentioning
confidence: 99%
“…Muitos estudos analisaram sujeitos com mordida aberta esquelética, comparando-os àqueles com padrões braquifaciais ou sujeitos com normoclusão (Cayley et al, 2000;Fayyat, 2000;Fujiki et al, 2000;2004;Lopes, 2000;Pacheco et al, 2000;Kawamura et al, 2003;Yamagushi e Sueishi, 2003;Degan, 2004;Bertoldi et al, 2005), no entanto, poucas vezes sujeitos com mordida aberta dentoalveolar têm sido incluídos (Ciccone de Faria et al, 2010;Piancino et al, 2012).…”
Section: Discussionunclassified
“…Vários estudos têm comparado a musculatura mastigatória de sujeitos com diferentes padrões verticais da face (Cayley et al, 2000;Fayyat, 2000;Fujiki et al, 2000;2004;Lopes, 2000;Pacheco et al, 2000;Kawamura et al, 2003;Yamagushi e Sueishi, 2003;Degan, 2004;Bertoldi et al, 2005). Poucas vezes sujeitos com mordida aberta dentoalveolar têm sido incluídos (Ciccone de Faria et al, 2010).…”
Section: Lista De Abreviaturasunclassified